2018
DOI: 10.3892/etm.2018.6961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microRNA‑370 on coronary atherosclerosis and its underlying mechanism

Abstract: As a global health problem, cardiovascular disease threatens the lives of human beings. It has been reported that microRNAs (miRs) are important in regulating coronary atherosclerosis. In the present study, the expression levels of miR-370 in peripheral blood mononuclear cells of patients with coronary atherosclerosis were significantly increased compared with healthy patients, as demonstrated by reverse transcription-quantitative polymerase chain reaction analysis. Additionally, the target of miR-370 was pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…These results suggested that circ_0010283 may regulate the progression of atherosclerosis by sponging miR-370-3p. In addition, the inhibitory role of miR-370-3p in atherosclerosis progression was observed, which was consistent with previous studies (19,32).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggested that circ_0010283 may regulate the progression of atherosclerosis by sponging miR-370-3p. In addition, the inhibitory role of miR-370-3p in atherosclerosis progression was observed, which was consistent with previous studies (19,32).…”
Section: Discussionsupporting
confidence: 92%
“…Emerging evidence has revealed a core position of miRNAs in the regulation of atherosclerosis progression (14,15). miR-370-3p has been reported to be associated with a number of human diseases including acute pneumonia, cerebral aneurysm and tuberculosis (16)(17)(18), and a previous study has demonstrated that miR-370-3p regulates coronary atherosclerosis progression (19). However, the Circular RNA circ_0010283 regulates the viability and migration of oxidized low-density lipoprotein-induced vascular smooth muscle cells via an miR-370-3p/HMGB1 axis in atherosclerosis precise mechanism of miR-370-3p in regulating atherosclerosis progression remains to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of TCDD-and PCB-induced atherosclerosis has been well characterized by many studies [21,23,39,40]. Emerging data continue to demonstrate the participation of miRNAs in atherosclerosis [41][42][43] and in biological responses induced by environmental pollutants [44][45][46]. However, there have been no previous reports on miRNA expression in TCDD-and PCB-induced atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among its putative target miRNAs, miR‐370 is the one with close association with the proliferation, apoptosis, and angiogenesis of vascular endothelial cells. The proliferation of HUVECs and formation of capillary‐like structures can be promoted by miR‐370 via inhibiting the expression of forkhead box 1 and maternally expressed gene 3 . But in retinal capillary endothelial cell, miR‐370 was reported to induce growth inhibition and apoptosis by reducing the expression of kinase insert domain‐containing receptor gene .…”
Section: Discussionmentioning
confidence: 99%